PELATIHAN “E-LEARNING FROM HOME” BAGI GURU PENDIDIKAN ANAK USIA DINI PADA MASA PANDEMIC COVID19 - Candra Asri Windarsih; Suhud Aryana; Ammy Ramdhania (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
The covid 19 pandemic outbreak continues to occur in various parts of the world including our country so that we immediately conduct a period of adaptation of new habits on all fronts, including the field of PAUD education, so that learning is all done at home. Learning From Home is carried out by parents, but curriculum, planning and assessment are still provided from the school. The purpose of the training is to know the steps that are used as guidelines in Learning From Home for teachers in the event of a pandemic, provide enlightenment and how to apply this method of devotion participatory approach with oriented teacher participation. The first step of the research is to analyze the situation, identification, objectives, problem solving plan, approach, implementation of training and evaluation. As a result of E-Learning From Home, teachers get new insights and enlightenment, teacher skills increase, media in demand in the form of quota-efficient applications, easy to use, accessible on mobile phones, and do not require a large memory.  This devotion will be followed up with the dedication of simple animation making in defense for early childhood